GAMBARAN KEPATUHAN MINUM OBAT PADA LANSIA HIPERTENSI MELALUI LITERATUR REVIEW (Politeknik Kesehatan Kemenkes Bandung, 2020)
ABSTRACT xii, 61 pages., 5 Chapters, 1 chart., 2 tables., 3 attachments Increasing human age, degenerative aging occurs which will have an impact on human health, such as the occurrence of non-communicable diseases (PTM), one of which is hypertension. The high incidence rate of elderly who experience hypertension can be controlled in 2 ways namely pharmacologically and non-pharmacologically. Pharmacologically the elderly who experience hypertension can control by obediently taking medication based on a prescription given by a doctor. The purpose of this study was to determine the description of medication adherence in elderly hypertension. This type of research is a descriptive study that provides an overview of the variables to be studied. The design used is a systematic literature review or often abbreviated as SLR in Indonesian called a systematic literature review. The data presented are secondary data. The results of the conclusions from the search of 4 journals are the first researcher results of taking medication in elderly hypertension as much as (45.7%), the second researcher as much as (59.6%), the third researcher as much as (45.14%) and the fourth researcher as many as (70%). It is recommended for the elderly to be able to comply with the therapy given by the doctor, the elderly can take counseling to understand the importance of complying with medication and the side effects of stopping medication themselves, the elderly can conduct consultations and recommendations for families to remind the elderly to take medication and provide support so that the elderly do not stop treatment. Key words: Hypertension, compliance, taking hypertension medication, elderly